Management for Preventing Ventilator-Associated Pneumonia at ICU Panti Rapih Hospital: A Clinical Case Study - Theresia, Siwi Ikaristi Maria (Nurse Media Journal of Nursing, 2016)
Background: Ventilator-Associated Pneumonia (VAP) is one kind of nosocomial infection that happens to patients who use mechanical ventilator and tracheostomy. Patients who are hospitalized in Intensive Care Unit (ICU) would have high risk onsuffering from Pneumonia.Objective: This paper aims to describe the interventions of nurses and to give recommendations for managing the VAP prevention using case study method.Methods: The data were collected from a patient who used mechanical ventilator and continued by observing and interviewing the nurses who took care of the patient.Results: The development of late onset of VAP was noticed after 96 hours. The observation result showed that there were fungi appeared after conducting a sputum culture from the patient. There was an increase of White Blood Cells on 72 hours after the intubation and the temperature increased until 37o C while the patient was using ventilator. Unfortunately, the nurses were not aware of the tendency of late onset VAP development in the patient.Discussion: Fungi are microorganism which causes VAP. The fungi were not proliferating because the patient had received early antibiotics for treatment. Early administration of antibiotics will prevent the development of VAP, but late VAP is associated with antibiotic-resistant organism. The significant increase of WBC count and the tendency of temperature while the patient was using ventilator were signs for developing infection. VAP can be prevented by conducting good oral hygiene every 2 hours using chlorhexidine 0.12% and using orogastric tube and ETT with sub glotticport to patients who use mechanical ventilator. Furthermore, positioning the patient’s head with 35o - 45o bed elevation is intended to prevent aspiration as well as checkingadequate endotracheal tube cuff of at least 20 cm H2.Conclusion: Awareness, responsibility, knowledge, skills of nurses are basis forinfection control especially for preventing VAP incidents.